Measuring Manufacturing Performance: A New Challenge for Managerial Accounting Research. - Kaplan, Robert S. (The Accounting Review, 1983)
ABSTRACT: Problems with the performance of U.S. manufacturing firms have become obvious in recent years. Japanese and Western European manufacturers are able to produce higher quality goods with fewer workers and lower inventory levels than comparable U.S. firms. The ability of foreign firms to become more efficient producers has gone largely unnoticed in the education and research programs of many U.S. business schools. A much greater commitment to understanding the factors critical to the success of manufacturing firms is needed. While an understanding of the determinants for successful manufacturing performance will require contributions from many disciplines, accounting can play a critical role in this effort. Accounting researchers can attempt to develop non-financial measures of manufacturing performance, such as productivity, quality, and inventory costs. Measures of product leadership, manufacturing flexibility, and delivery performance could be developed for firms bringing new products to the marketplace. Expanded performance measures are also necessary for capital budgeting procedures and to monitor production using the new technology of flexible manufacturing systems. A particular challenge is to deemphasize the current focus of senior managers on simple, aggregate, short-term financial measures and to develop indicators that are more consistent with long-term competitiveness and profitability.